Analisis Komparasi User Experience Pada Aplikasi OVO dan DANA dengan Metode User Experience Questionnaire - Adawiyah, Rabiatul; Oktadini, Nabila Rizky (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of digital wallet technology, especially through smartphone platforms such as OVO and DANA, has changed the financial transaction landscape significantly. Both applications function as digital payment tools, but they have differences in features, layout, colors and performance. User experience (UX) is the basis of research because it is a crucial factor in the success of a product or service. By comparing the two applications through UEQ, we can provide valuable insight into the strengths and weaknesses of each platform, as well as provide a broader view of trends and best practices in user experience design in the digital payments industry, and hope to gain a deeper understanding of these aspects. -which aspects influence user satisfaction and how the two compare. The UEQ method will help identify the strengths and weaknesses of each application in terms of attractiveness, efficiency, perspicuity, dependability, stimulation and novelty. Thus, getting more comprehensive insights for application developers and other stakeholders to improve the quality of service and user experience of both applications. The User Experience Questionnaire (UEQ) questionnaire was given to 115 respondents. The results of the UEQ questionnaire on the OVO and DANA applications show positive evaluation aspects given to both applications. The mean value of the OVO application based on the aspects of attractiveness (1.99), efficiency (2.07), dependability (1.77), stimulation (1.79), novelty (1.75) obtained the